Evaluation of CPS compliance with legally required review of investigations by CAPs. (October 2021) - Murray, Liza; Yoder, Joseph; Cantu, Marissa; Anderst, Jim
Abstract: Background: There is significant variability in Child Protective Services (CPS) utilization of medical-forensic experts. In 2016, Missouri legislation (HB 1877) mandated that CPS investigators submit screening forms to a Child Abuse Pediatrician (CAP) to review children < 4 years investigated for abuse. Compliance with this mandate is unknown. Objective: To measure compliance with HB 1877, hypothesizing that urban counties would have better compliance than rural counties. Participants and setting: This retrospective study included evaluation of screening forms completed by Missouri CPS and submitted to Missouri CAPs during February, July and September of 2017. Methods: Compliance was measured in three ways. Compliance Measure 1 (CM1) was the number of screening forms versus the number of eligible CPS investigations. Compliance Measure 2 (CM2) was the average number of days from an abuse report until form submission, and Compliance Measure 3 (CM3) was the percentage of forms with complete information. Urban and rural counties were classified by 2010 census data. t -Tests were used to compare compliance measures between urban and rural counties. Results: Overall compliance with CM1 was 69% with 1496 screening forms submitted and 2170 child maltreatment investigations for children less than 4 years of age. For CM2, mean days from abuse report to form submission was 30 days. For CM3, 60.5% of statewide forms were complete. There was no significant difference between rural and urban county compliance. Conclusions: Limited compliance with HB 1877 demonstrates the necessity of continued monitoring and improvement for optimal efficacy of legal mandates. Highlights: Medical-forensic input can improve responses to child maltreatment. Legal mandates may improve collaboration between CPS and CAPs. Compliance with legally mandated CPS-CAP collaboration in Missouri was variable. Effective implementation of legislation requires ongoing monitoring and evaluation.